Three-dimensional momentum imaging of dissociation in flight of metastable molecules. (4th October 2017) - Jochim, Bethany; Erdwien, Reid; Malakar, Y; Severt, T; Berry, Ben; Feizollah, Peyman; Rajput, Jyoti; Kaderiya, B; Pearson, W L; Carnes, K D; Rudenko, A; Ben-Itzhak, I
Abstract: We investigate dissociation in flight of metastable molecular dications formed by ultrashort, intense laser pulses using the cold target recoil ion momentum spectroscopy technique. A method for retrieving the lifetime(s) of the transient metastable state(s) as well as the complete three-dimensional momenta of the dissociating fragments is presented. Specifically, we demonstrate and discuss this approach by focusing on dissociation in flight of the ethylene dication going to the deprotonation channel. Two lifetimes are found to be associated with this process, C2 H 4 2 + → C2 H3 + + H + : τ 1 = 202 ± 10 ns and τ 2 = 916 ± 40 ns. For the corresponding channel in deuterated ethylene, lifetimes of τ 1 = 269 ± 29 ns and τ 2 = 956 ± 83 ns are obtained.